Forty-year single-center experience of Burkholderia cystic fibrosis airway infections - Burkhard Tümmler; Jutta Ulrich; Ludwig Sedlacek (International Journal of Infectious Diseases, 2024)
Objectives: To resolve the epidemiology of airway infections with Burkholderia cepacia complex (Bcc) in patients with cystic fibrosis (pwCFs) over 40 years at a single treatment center. Methods: All Bcc and Burkholderia gladioli airway isolates were collected from pwCFs who presented at the cystic fibrosis outpatient and the lung transplantation clinics from 1983 to 2022. Results: The collection of 1205 strains is dominated by B. multivorans (56%), followed by B. cenocepacia (16%), B. stabilis (10%), and B. orbicola (9%). A total of 27 pwCFs experienced a single self-limiting episode of airway infection with Bcc. A total of 13 pwCFs were harboring Bcc for 1.7-13.6 years and 15 pwCFs were persistently infected with Bcc. A total of 16 Bcc-positive pwCFs received a lung transplant. Fatal post-transplant sepsis happened in one patient with B. multivorans, two with B. cenocepacia, and two with B. orbicola. Conclusions: After the first acquisition of Bcc, transient carriage was 2.7 times more frequent than persistent colonization. Infections with B. cenocepacia or B. orbicola confer a higher risk for post-transplant sepsis than an infection with B. multivorans.